Is foliar tissue drying and grinding required for reliable and reproducible extraction of total inorganic nutrients? A comparative study of three tissue preparation methods - Minocha, Rakesh; Long, Stephanie (Frontiers in Plant Science, 2022)
In response to abiotic and abiotic stress or experimental treatment(s), cellular concentrations of inorganic nutrients and metabolites in the foliage of plants/trees often change in concert to maintain a homeostatic balance within the cell's environment that allows for normal functions to carry on. Therefore, whenever possible, we should evaluate changes in cellular chemistry, metabolism, and gene expressions using a common pool of tissue. This will help expand our understanding of how these variables function together to maintain cellular homeostasis. Currently, tissue for metabolic and molecular work is often kept frozen in small quantities, while tissue for inorganic nutrients extraction (collected separately) is first oven-dried and then ground in some type of mill. The objective of the present study was to evaluate whether wet (previously frozen)-intact tissue would be a suitable substitute for dried-ground tissue commonly used for the extraction of total foliar nutrients. We compared quantities of nutrients extracted from wet-intact, dried-intact, and dried-ground tissues taken from a common pool (also used for molecular work) of previously frozen foliage of of black oak (Quercus velutina L.), sugar maple (Acer saccharum Marshall), red spruce (Picea rubens Sarg.), and white pine (Pinus strobus L.). Data pooled across several collection periods presented in this report suggest that the extractions of nutrients were comparable for all methods and all species except for higher yields of Ca, Mg, K, and P in sugar maple and K and P in black oak with wet-intact tissue extraction compared to dried-intact and dried-ground tissue extractions. In hardwoods, the yield from wet-intact foliage was seemingly higher for September 2014 and July 2015 collections compared to the other two methods, although in June 2014 it was more comparable. For conifers, no major differences were apparent between methods for various collection times. Based on the data presented here, it may be concluded that drying and grinding samples may not be necessary, making analyses more efficient and versatile.